Public violence in Islamic societies : power, discipline, and the construction of the public sphere, 7th-19th centuries C. E. - Lange, Christian Robert, 1975-; Fierro, Ma. Isabel (Maria Isabel) (Edinburgh : Edinburgh University Press, 2009)
PSZJBL